Disabled people are left behind the information age: are the gap getting bigger? - Khalid, Nur Ajrun; Yusof, Rohana (2016)
Rapid progress of Information Communication Technology (ICT) will accelerate the distribution of information from government to the people; however the monopoly of technology ICT services will lead to inequality of information distribution in between of normal people and disabled people.Embrace with the inequality of ICT distribution directly make the group of disabled people left behind at the information age, or the situation also known as digital divide.Hence, this article attempts to identify and examine the issues facing by disabled people in order to catch up the fast diffusion of ICT.